Konsep Mediasi Dalam Penyelesaian Syiqāq (Studi Komparatif Fiqh al-Syāfi’iyyah dan Hukum Positif) - Mahmudi Hanafiah (Fakultas Syariah dan Ekonomi Islam, 2021)
Marriage is expected to be a way to get a peaceful life. However, this expectation is not always fulfilled. Shiqāq often occurs in the household. Islam orders mediation in the event of shiqāq. In positive law in Indonesia, mediation is also one of the obligations in litigation in the Court. The research is entitled Mediation Concept in Shiqāq Settlement (Comparative Study of Fiqh al-Syāfi'iyyah and Positive Law). The problem studied is how the concept of mediation in the settlement of syiqāq according to fiqh al-syāfi'iyyah and positive law and how the mediation comparison between the two is. This research is library research with qualitative method and normative approach which is descriptive-analytic-comparative. The author concludes that mediation of shiqāq cases is an obligation according to fiqh al-syāfi'iyyah. Mediation is carried out by presenting representatives from the parties called ẖakam to convey the will of each party. The appointment of representatives of the parties is an obligation. The judge divorces husband and wife if according to a report from the representative the two cannot be reunited. Positive Law also makes mediation an obligation, by involving disputing husband and wife in mediating, without presenting other parties. Fiqh al-Syafi'iyyah and Positive Law both require mediation. Fiqh al-Syafi'iyyah conducts mediation by not directly involving the parties, but with their respective representatives, while positive law involves the parties directly in mediation. Mediation according to fiqh al-Syafi'iyyah cannot return a husband and wife who have been divorced outside the court. Meanwhile, positive law assumes that divorce outside the court does not occur so that husband and wife are declared to have never divorced at all if the mediation event succeeds in reconciling them. Key Words: mediation, judge, syiqāq, ẖakam.